Peningkatan Kualitas Laporan Keuangan Dengan Software MYOB Accounting Versi 16 - Sri Murni; Noraeni Noraeni (LPPM Universitas Bina Sarana Informatika, 2020)
Computer technology has helped many people in overcoming problems that occur including in the fields of business and accounting. The object of research is CV. Malianury Graffiti which is a printing service company. The company records and presents reports using the Microsoft Excel application. The final report is only in the form of sales reports and financial transaction records. Thus this company performs manual calculations to determine the company's profit / loss. The purpose of this study is to provide solutions to problems that occur and compare the conventional recording with recording using accounting software, MYOB Premier V.16 on CV. Malianury Graffiti. The research method used in the form of data collection methods are observation, interviews and literature study. It is hoped that this research can facilitate the company in processing transactions into financial statements, improving the results of financial statements, useful for related parties in analyzing financial statements and in decision making.